The Effectiveness of Posyandu Cadre Empowerment on Improving Knowledge, Attitudes, and Compliance of Mothers of Under-Five Children in Routine Growth Monitoring - Tri Afrinia; Suharmanto; Susianti; Dyah Wulan Sumekar Rengganis; Betta Kurniawan (Institut Kesehatan YARSI Mataram, 2026)
Routine child weighing at Posyandu is essential for monitoring growth and early detection of nutritional problems; however, maternal participation remains suboptimal due to inadequate knowledge, negative attitudes, and poor compliance. Although Posyandu cadres play a central role in community-based child health services, evidence regarding the effectiveness of cadre empowerment in improving maternal compliance remains limited. This study aimed to analyze the effectiveness of Posyandu cadre empowerment in improving mothers' knowledge, attitudes, and compliance with routine child weighing in the Pringsewu Community Health Center working area, Indonesia, in 2026. A quasi-experimental pretest–posttest control group design was conducted among 82 mothers of children under five selected using proportional stratified random sampling. Data were collected using a validated and reliable questionnaire and analyzed using paired t-tests and the McNemar test. The intervention significantly increased knowledge (mean difference = 5.67; 95% CI: 5.14–6.21; Cohen's d = 2.33; p < 0.001), attitudes (mean difference = 11.33; 95% CI: 10.93–11.73; Cohen's d = 6.16; p < 0.001), and compliance (p < 0.001; matched OR = 34.00; 95% CI: 4.65–248.38), whereas no significant changes were observed in the control group. These findings indicate that Posyandu cadre empowerment is an effective promotive and preventive strategy for strengthening maternal participation in routine child health monitoring